PHYSICAL EDUCATION AND ORGANIZATION OF SERIOUS ENTERTAINMENT CENTERS IN SCHOOL. STUDY FOR IMPROVEMENT OF PROCUREMENT OF CIVIL POWERS AND SOCIAL INCLUSION (Fiep Bulletin - online, 2011)
This research is in line with the work that the Department of Music and Corporal Expression, University of Barcelona has been carrying out studies and social inclusion through the practice of physical and sports activities. The school population is becoming more diverse as a result of immigration. The cultural and social enrichment, one can see threatened by the lack of preparation and support, theoretical and practice of teaching teams. This work was to study the reality of school standards and inclusion of newly arrived immigrant students from the perspective of the spontaneous performance of the students themselves, seeking learning indicators of civic skills and social impacts inside and outside of class time. The starting point is the educational experiences found in the previously developed projects, and initiatives of the European Union countries. In the present study observed that physical activity results in a valuable way to leverage the inclusion and social cohesion, it is intentionally directed toward this purpose. Studied the relationship between the organization of an activity in public spaces free school and the acquisition of social skills and drive to facilitate the inclusion of students of diverse cultural origin. The research was based primarily on document analysis and observations participating. Selected three educational settings with a high percentage of immigrant pupils, were applied in three different driving proposals: the first category, develops in a large space with children's early childhood education, which carries out the spontaneous play. There is a structure created through the material, space and time, but not really a game conditioning or directed. The second context is the observed break time in a college of Primary Education (Elementary 1). The third context is the one class session of Physical Education, an Institute for Secondary Education (Elementary 2). Data analysis was assisted by NVivo computer program (v2). A clear conclusion that emerges relates to the capability of driving cooperative activities. The inclusion of newly arrived immigrant students are more likely when students have to achieve a common goal. This was observed in driving situations proposed in child centers, and also in some activities performed by the student's school. However, it also became evident in situations where the immigrant children was unrelated to the rest of the group-class. These situations reflect the informal and spontaneous behaviors that occur in the breaks, as well as activities aimed at stimulating little, or too far from their previous knowledge and skill levels present.
Keywords: inclusion; play; physical education spaces; immigrants